The atomic gas of star-forming galaxies at z ∼ 0.05 as revealed by the Five-hundred-meter Aperture Spherical Radio Telescope - Cheng, Cheng; Ibar, Edo; Du, Wei; Molina, Juan; Orellana-Gonzáles, Gustavo; Zhang, Bo; Zhu, Ming; Xu, Cong Kevin; Wu, Shumei; Cao, Tianwen; Huang, Jia-Sheng; Leiton, Roger; et al. (Astronomy and astrophysics (Berlin), 2020)
Context. We report new H I observations of four z ∼ 0.05 VALES galaxies undertaken during the commissioning phase of the Five-hundred-meter Aperture Spherical Radio Telescope (FAST). Aims. FAST is the largest single-dish telescope in the world, with a 500 m aperture and a 19-Beam receiver. Exploiting the unprecedented sensitivity provided by FAST, we aim to study the atomic gas content, via the H I 21 cm emission line, in low- z star formation galaxies taken from the Valparaíso ALMA/APEX Line Emission Survey (VALES). Together with previous Atacama Large Millimeter/submillimeter Array (ALMA) CO( J = 1−0) observations, the H I data provides crucial information to measure the gas mass and dynamics. Methods. As a pilot H I galaxy survey, we targeted four local star-forming galaxies at z ∼ 0.05. In particular, one of them has already been detected in H I by the Arecibo Legacy Fast ALFA survey (ALFALFA), allowing a careful comparison. We use an ON-OFF observing approach that allowed us to reach an rms of 0.7 mJy beam −1 at a 1.7 km s −1 velocity resolution within only 20 min ON-target integration time. Results. In this Letter, we demonstrate the extraordinary capability of the FAST 19-beam receiver to push the detectability of the H I emission line of extra-galactic sources. The H I emission line detected by FAST shows good consistency with the previous Arecibo telescope ALFALFA results. Our observations are put into context with previous multi-wavelength data to reveal the physical properties of these low- z galaxies. We find that the CO( J = 1−0) and H I emission line profiles are similar. The dynamical mass estimated from the H I data is an order of magnitude higher than the baryon mass and the dynamical mass derived from the CO observations, implying that the mass probed by dynamics of H I is dominated by the dark matter halo. In one case, a target shows an excess of CO( J = 1−0) in the line centre, which can be explained by an enhanced CO( J = 1−0) emission induced by a nuclear starburst showing high-velocity dispersion.